Documentary Media and Religious Communities Journal for Religion, Film and Media - Marie-Therese Mäder (Journal for Religion, Film and Media, 2015)
The article considers four spaces where media processes involve religious communities and agents: the spaces of production, of representation, of media communication, and of distribution network and institutional framework for circulation. These four spaces systematise the research question posed to the specific source. Furthermore the concept documentary media as viewed from a semio-pragmatic perspective is introduced. Discussion of the commercial series I'm a Mormon shows how different modes define documentary media according to the four spaces.